Acute coronary syndrome in young patients: clinical features and risk factors - I. V. Ponomarenko; I. A. Sukmanova; V. A. Elykomov (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To study the clinical features and risk factors (RF) associated with the development of acute coronary syndrome (ACS) in young patients.Material and methods. The study included 474 patients with ACS. Depending on age, patients were divided into 2 groups. The first group consisted of 299 patients of young age (25-44 years), the comparison group consisted of 175 patients of mean and old age (45-74 years). Clinical and anamnestic data, parameters of general clinical and biochemical tests, electrocardiography, echocardiography and coronary angiography were determined in all patients, and polymorphisms in FII G20210-A, FV G1691-A, MTHFR C677-T genes were determined in 116 patients. The control group consisted of 53 healthy volunteers.Results. ACS in patients <45 years old is most common in men. The number of women with ACS increases as elder patient is. The incidence of myocardial infarction (MI) and unstable angina, ST-elevated MI and non ST-segment elevation MI, Q-wave and non-Q-wave MI had no differences between patients of the younger and older age groups. In younger patients, anterior localization of myocardial infarction was more common, in mean and old patients — posterior. Complications of MI in young patients were less common than in the comparison group. In patients of mean and old ages, acute coronary event was preceded by a clinic of angina, in young patients most often it was the debut of coronary artery disease. It was revealed that single-vessel coronary lesion is more characteristic for young patients, for the elderly patients — two-vessel and multi-vessel. Pathology of the anterior descending coronary artery prevailed in both groups of patients. Most patients in both groups underwent myocardial revascularization. MI as a result of coronary artery thrombosis happened more often in young patients. The most significant RF associated with the ACS development were: increased total cholesterol and low density lipoproteins, decreased high density lipoproteins, increased body mass index, smoking, polymorphism of MTHFR-homozygote, hereditary tainted with smoking, aggravation in combination with F5-homozygote, hereditary tainted in combination with MTHFR-homozygote, hereditary tainted in combination with smoking and MTHFR homozygote.Conclusion. We identified clinical features and RF, mostly associated with the development of ACS in patients <45 years of age. The results can serve as additional indicators showed the risk of ACS development.